Organocatalytic Synthesis of Tetrahydroquinolines from α,β-Unsaturated Ketones via 1,5-Hydride Transfer/Cyclization - Kim, Dae Young (Bulletin of the Korean Chemical Society, 2013)
KCI Citation Count: 23